Sixth man surprise - Maddox, Jake; Pryor, Shawn (Jake Maddox graphic novels., 2023)
Thirteen-year-old Devante Briggs loves basketball, but now he is just the sixth man off the bench for his school team, putting up with the snide remarks of some of the other players--until an outbreak of food poisoning gives him his chance to show off his skills.